Prevalence, Change and Burden of Systemic Corticosteroid Use in Type 2 Inflammation Associated Diseases Over 25 Years – A Nationwide Danish Study - Håkansson KEJ; Skov IR; Andersen SAW; Ali Z; Løkke A; Ibsen R; Hilberg O; Meteran H; Johnsen CR; Backer V; Ulrik CS (Journal of Asthma and Allergy, 2025)
Kjell Erik Julius Håkansson,1,2 Inge Raadal Skov,3 Steven Arild Wuyts Andersen,4,5 Zarqa Ali,6 Anders Løkke,7,8 Rikke Ibsen,9 Ole Hilberg,7,8 Howraman Meteran,1 Claus R Johnsen,10 Vibeke Backer,4,5 Charlotte Suppli Ulrik1,5 1Department of Respiratory Medicine, Copenhagen University Hospital - Hvidovre, Hvidovre, Denmark; 2Department of Respiratory Medicine, Copenhagen University Hospital - Bispebjerg, Copenhagen, Denmark; 3Department of Medicine, Little Belt Hospital, Kolding, Denmark; 4Department of Otorhinolaryngology – Head & Neck Surgery and Audiology, Copenhagen University Hospital - RigsHospitalet, Copenhagen, Denmark; 5Institute of Clinical Medicine, University of Copenhagen, Copenhagen, Denmark; 6Department of Dermatology, Copenhagen University Hospital - Bispebjerg, Copenhagen, Denmark; 7Department of Medicine, Lillebælt Hospital, Vejle, Denmark; 8Department of Regional Health Research, University of Southern Denmark, Odense, Denmark; 9i2Minds, Aarhus, Denmark; 10Allergy Clinic, Copenhagen University Hospital - Gentofte, Gentofte, DenmarkCorrespondence: Kjell Erik Julius Håkansson, Respiratory Research Unit 237, Copenhagen University Hospital – Hvidovre, Kettegård Allé 30, Hvidovre, 2650, Denmark, Email kjell.erik.julius.haakansson@regionh.dkBackground: Systemic corticosteroid use in type 2 inflammation-associated diseases including asthma, atopic dermatitis, allergic rhinitis, and chronic rhinosinusitis has been associated with adverse outcomes, and corticosteroid-sparing treatments are available.Objective: Assess temporal changes in systemic corticosteroid use and the impact of type 2 inflammation multimorbidity (eg multiple concurrent type 2 inflammation-associated diseases) and specialist assessment on systemic corticosteroid exposure.Methods: Using nationwide databases, all Danish adults with asthma, atopic dermatitis, allergic rhinitis, or chronic rhinosinusitis, based on hospital diagnoses or redeemed prescriptions between 1997 and 2021 were included in an open, serial cross-sectional cohort.Results: Over 25 years, a total of 2,151,209 Danish adults were included. Of those with a single diagnosis (type 2 inflammation monomorbidity),13.9% had asthma, 19.2% allergic rhinitis, 52.9% atopic dermatitis, and 14.0% chronic rhinosinusitis. In terms of type 2 inflammation multimorbidity, 75.1% of included individuals had one, 21.3% two and 3.5% three diagnoses, respectively. Overall, 9.6% of type 2 monomorbid individuals redeemed systemic corticosteroids, with asthma (16.5%) and atopic dermatitis (6.0%) having the highest and lowest prevalence of use. Systemic corticosteroid use peaked in 2006 (10.6%) and was lowest in 2020 (7.2%). Exposure > 5 mg prednisolone/day was constant around 15% overall among users. Type 2 inflammation multimorbidity was associated with increases in systemic corticosteroid use at 9.6%, 16.0% and 20.9% for one, two and three diagnoses, respectively. A median referral delay of 4.1 [8.1] years from first systemic corticosteroid redemption to specialist assessment was seen. Specialist assessment led to a 64.9% reduction in median annual systemic corticosteroid exposure overall.Conclusion: In type 2 inflammation associated diseases, systemic corticosteroid use remains common despite the introduction of corticosteroid-sparing treatments. Timely referrals to specialist assessment could reduce the overall systemic corticosteroid exposure.Plain Language Summary: This study looked at how often a type of medicine called systemic corticosteroids is used by people with certain health conditions related to inflammation such as asthma, allergies, atopic eczema and chronic rhinosinusitis, in Denmark over the past 25 years. Systemic corticosteroids (eg prednisolone) are strong medications that help reduce inflammation in the body. While they can be very effective towards severe symptoms, long-time use can lead to serious health problems, including weight gain, diabetes, and weakened bones.The study aimed to determine how many patients with these inflammatory diseases were using systemic corticosteroids and how this has changed over time. They found that overall, about 9.6% of patients with one of these conditions used systemic corticosteroids. Among these patients, asthma patients had the highest usage at 16.8%, while those with atopic eczema had the lowest at 6.0%.Overall, the study observed a decrease in the use of these medications since 2006, especially during the COVID-19 pandemic. However, patients with multiple conditions, such as having both asthma and allergies, tended to rely more on systemic corticosteroids. Importantly, the study showed that patients who visited a specialist after starting systemic corticosteroids were able to significantly reduce their use of these medications, but many patients had to wait several years before being seen by a specialist.In conclusion, even though there are safer treatments available, many people still depend on systemic corticosteroids. Timely help from specialists can assist in reducing the need for these medications and the associated health risks.Keywords: prednisolone, allergic rhinitis, asthma, chronic rhinosinusitis, atopic dermatitis, corticosteroid sparing